Enhanced thermoelectric performance in the Rashba semiconductor BiTeI through band gap engineering. (1st February 2016) - Wu, Lihua; Yang, Jiong; Zhang, Tiansong; Wang, Shanyu; Wei, Ping; Zhang, Wenqing; Chen, Lidong; Yang, Jihui
Abstract: Rashba semiconductors are of great interest in spintronics, superconducting electronics and thermoelectrics. Bulk BiTeI is a new Rashba system with a giant spin–split band structure. 2D-like thermoelectric response has been found in BiTeI. However, as optimizing the carrier concentration, the bipolar effect occurs at elevated temperature and deteriorates the thermoelectric performance of BiTeI. In this paper, band gap engineering in Rashba semiconductor BiTeI through Br-substitution successfully reduces the bipolar effect and improves the thermoelectric properties. By utilizing the optical absorption and Burstein–Moss-effect analysis, we find that the band gap in Rashba semiconductor BiTeI increases upon bromine substitution, which is consistent with theoretical predictions. Bipolar transport is mitigated due to the larger band gap, as the thermally-activated minority carriers diminish. Consequently, the Seebeck coefficient keeps increasing with a corresponding rise in temperature, and thermoelectric performance can thus be enhanced with a ZT = 0.5 at 570 K for BiTeI0.88 Br0.12 .